A Multi-Criteria Decision Making Approach for E-Commerce: An Evolutionary Study with Spring Boot Implementation - Davis, F. D.; Hendricks, S.; Adriana, M. N.; Ahmad, S. Z.; Lucas, G. A.; Ahmed, J. U. (2025 International Conference on Pervasive Computational Technologies (ICPCT), 2025)
The lockdown period witnessed a significant boom in Electronic Commerce (E-Commerce) websites, enabling people to make purchases safely and securely from their homes. A substantial portion of the population now relies on this industry, particularly in the B2C (Business-to-Customer) segment, where businesses operate online and offer direct services to customers. This study explores the integration of multi-criteria decision-making (MCDM) methodologies to provide customers with diverse product options and sufficient time to make informed purchasing decisions. The implementation employs React.js for frontend development, Cascading Style Sheets (CSS) for design enhancement, Java Spring Boot for backend development, and MySQL for database management.